Theological Originality - Burke, T. E. (Religious studies, 1976)
In contemporary discussion of the philosophy of religion, or for that matter of any branch of philosophy, the names of Whitehead and Wittgenstein are not often linked. Whitehead's later work is, for the most part, treated as a rather specialized interest, an attractively under-cultivated field for the enterprising thesis-writer perhaps, but well away from the main centres of current philosophical activity. And what he has to say about specifically religious or theological issues (apart from the often quoted or misquoted Religion is what the individual does with his own solitariness)1 becomes simply one ramification of an ingenious but somewhat eccentric system. Nonetheless, there is at least this much justification for considering it in relation to the much more influential and widely discussed views of Wittgenstein. Whitehead has some original things to say about God, Wittgenstein some original reasons for thinking that Whitehead's brand of originality is here radically misplaced. And the possibility or otherwise of such theological originality is an issue of very considerable importance for the philosophy of religion.